Pelaksanaan Fardhu Kifayah Bagi Jenazah yang Terinfeksi Covid-19 di Rumah Sakit Putri Bidadari Kabupaten Langkat (Analisis Fatwa Mui No 18 Tahun 2020 Pada Fikih Wabah) - Muhammad Harun Al Rasyid Rasyid; Muhammad Syahnan Syahnan; Hafsah Hafsah (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2022)
The purpose of the study was to determine the implementation of fardhu kifayah for corpses infected with COVID-19 at Putri Bidadari Langkat General Hospital and to find out the obstacles or obstacles in implementing fardhu kifayah for bodies infected with COVID-19 at Putri Bidadari Langkat General Hospital. The type of research used is empirical research. Empirical research is a study that views law as a reality, including social reality, cultural reality and others. Data collection techniques by means of observation, interviews, literature review and documentation. The data analysis technique in this study uses analytical methods, content analysis techniques aim to explore the content or meaning in the form of documents, literary works, articles and so on in the form of unstructured data. Data absence technique by means of triangulation of sources and methods. The results of this study indicate that the implementation of the Covid-19 corpse at RSU Putri Bidadari Langkat is the basis for the management of Muslim bodies (tajhiz al-jana'iz) exposed to COVID-19, especially in bathing and worshiping. must be carried out according to medical protocol and carried out by the Purti Bidadari Langkat General Hospital while still taking into account the provisions of Islamic law. Meanwhile, praying and burying him is carried out as usual by Islamic law while maintaining health protocols so as not to be exposed to COVID-19. Meanwhile, the inhibiting factor or obstacle in implementing the fardhu kifayah of the Covid-19 corpse is the family's refusal to handle the Covid-19 corpse.